The Development Of A Project-Based Contextual Learning Model For The Course On Human-Computer Interaction - Putra, Andi; Zulkifli (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
This study aims to develop and implement a Project-Based Contextual Learning (PBCL) model to enhance the effectiveness of teaching the Human–Computer Interaction (HCI) course. The research employed a Research and Development (R&D) approach using the 4-D model, which includes the stages of Define, Design, Develop, and Disseminate. The PBCL model was designed to integrate contextual learning principles with project-based tasks, enabling students to connect theoretical knowledge with practical applications. The results indicate a significant improvement in student learning outcomes. The average score increased from 61.5 in the pretest to 84.7 in the posttest, with a gain score of 23.2 points. Competency in interface design also improved, with the proportion of competent students rising from 36% to 82%. Observations showed higher levels of engagement and collaboration, while survey responses revealed that 87% of students perceived the PBCL model as meaningful, motivating, and relevant to real-world contexts. In conclusion, the PBCL model effectively enhances cognitive achievement, practical skills, and student motivation in the HCI course. This model offers a promising pedagogical framework that can be applied to other technology-related courses requiring the integration of conceptual understanding and practical competencies.